Pengaruh Strategi Pembelajaran Berbasis Masalah dan Minat Belajar Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa pada Materi Sistem Pencernaan Makanan Manusia di MAS Amaliyah Sunggal - Naputri, Ridho Fenni; Syarifuddin, Syarifuddin; Djulia, Ely (Jurnal Pendidikan Biologi, 2016)
This study was aimed to determine effect on: (1) Problem based learning strategy toward critical thinking skills; (2) Learning interest toward critical thinking skills; (3) Interaction between problem based learning strategy and learning interest toward critical thinking skills; (4) Problem based learning strategy toward studentsâ learning outcomes; (5) Learning interest toward studentsâ learning outcomes; and (6) Interaction between problem based learning strategy and learning interest toward studentsâ learning outcomes. Subjects in this study are taken as much as 3 classes is determined by a cluster random sampling. Determined learning class in research is 2 classes with sample of 38 people per class. . Based on the results show that there are significant effect on (1) Learning model toward critical thinking skills which obtained Fcount>Ftable (6,971>2,50) and probability value is 0,010<0,05; (2) Learning interest toward critical thinking skills which obtained Fcount>Ftable (24,949>2,50) and probability value is 0,000<0,05; (3) Interaction between learning model and learning interest toward critical thinking skills which obtained Fcount>Ftable (4,140>2,50) and probability value is 0,046<0,05; (4) Learning model toward studentsâ learning outcomes which obtainde Fcount>Ftable (25,269>2,50) and probability value is 0,000<0,05; (5) Learning interest toward studentsâ learning outcomes which obtained Fcount>Ftable (13,888>2,50) and probability value is 0,000<0,05; and (6) Interaction between learning model and learning interest toward studentsâ learning outcomes which obtained Fcount>Ftable (4,291>2,50) and probability value is 0,042<0,05. Based on this study can conclude that there are significant effect of strategy, interest, and interaction between learning strategy and learning interest toward critical thinking skills and studentsâ learning outcomes on the topic in digestive system of human at MAS Amaliyah Sunggal. This cases are expected to provide information for teachers and schools to use problem based learning strategy and learning interest to improve critical thinking skills and studentâs learning outcomes.